Citizenship Socialization Process and National Integration: Appraisal of Civics and General Studies Courses in Nigerian Schools - Sirajo Alhaji Ladan; Samaila Bello (Interdisciplinary Journal of Education)
Efforts at nation-building in Nigeria are hindered by various social problems linked to the low level of national integration among its religiously, regionally and ethnically diverse population. This paper examined citizenship socialization courses and subjects at the three (3) levels of education (Basic, Secondary and Tertiary) in Nigeria that are designed to promote national integration. The courses and subjects include Citizenship Education, Civic Education and General Studies (Peace Studies and Conflict Resolution and Nigerian Peoples and Culture). Similarly, key concepts such as socialization, citizenship socialization courses and national integration are conceptualized. The Functionalists sociological perspective was adopted as a theoretical framework to establish the link between citizenship socialization courses and subjects and promotion of national integration. However, despite the link or potential of citizenship education in raising the level of national integration, the paper identified some constraints on the extent to which citizenship socialization courses and subjects promote the desired national integration among the people of Nigeria. These challenges include the current assessment methods in schools, which focus on testing cognitive rather than affective abilities, the problem of inadequate funding of education in general, large size lecture halls and other poor teaching and learning conditions and Low credit units or time on the time table on specific curriculum subjects and courses meant citizenship socialization for national integration. To address these challenges, the paper suggests diversifying assessment and evaluation methods, among other strategies, to improve the teaching of citizenship socialization courses and promote national integration in Nigeria.